Experience that Much Work Produces Many Reinforcers Makes the Sunk Cost Fallacy in Pigeons: A Preliminary Test - Fujimaki, Shun; Sakagami, Takayuki (Frontiers in Psychology, 2016)
The sunk cost fallacy is one of the irrational choice behaviors robustly observed in humans. This fallacy can be defined as a preference for a higher-cost alternative to a lower-cost one after previous investment in a higher-cost alternative. The present study examined this irrational choice by exposing pigeons to several types of trials with differently illuminated colors. We prepared three types of nonchoice trials for experiencing different outcomes after presenting same or different colors as alternatives and three types of choice trials for testing whether pigeons demonstrated irrational choice. In nonchoice trials, animals experienced either of the following: (1) no reinforcement after the presentation of an unrelated colored stimulus to the alternatives used in the choice situation, (2) no reinforcement after investment in the lower-cost alternative, or (3) reinforcement or no reinforcement after investment in the higher-cost alternative. In choice trials, animals were required to choose in the following three situations: (A) higher-cost vs. lower-cost alternatives, (B) higher-cost vs. lower-cost ones after some investment in the higher-cost alternative, and (C) higher-cost vs. lower-cost alternatives after the presentation of an unrelated colored stimulus. From the definition of the sunk cost fallacy, we assumed that animals would exhibit this fallacy if they